Detection system of multi-track intelligent inspection robot for urban rail vehicles - WU Hongbo; QIU Weiming; WANG Jing; ZHU Linsen (机车电传动)
The multi-track intelligent inspection robot detection system of urban rail vehicles realized automatic detection of the bottom and both sides of subway vehicles by adopting intelligent robot technology, SLAM (Simultaneous Localization and Mapping) technology, multi-degree-of-freedom flexible cooperative manipulator control technology, high-definition optical imaging technology and AI (Artistic Intelligence) algorithm, as well as automatic early warning of abnormal situations such as deformation, looseness, missing and foreign bodies of key components of vehicle running gear. At the same time, combined with vehicle maintenance scheduling and intelligent multi-track switching device, the robot could switch freely among multi-tracks in the maintenance warehouse, which improved the application efficiency of the robot in the maintenance process. The actual application of subway site shows that the application of intelligent inspection robot can optimize the maintenance technology of subway vehicles, prolong the maintenance interval, help improve the quality and efficiency of subway vehicle maintenance, and has very important social and economic value.